2005
DOI: 10.1291/hypres.28.1017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a New Calcium Channel Blocker, Azelnidipine, on Systemic Hemodynamics and Renal Sympathetic Nerve Activity in Spontaneously Hypertensive Rats

Abstract: Antihypertensive treatment with dihydropyridine calcium channel blockers elicits sympathetic nerve activation, which may contribute to cardiovascular events. However, recent clinical studies showed that treatment with azelnidipine, a new dihydropyridine calcium channel blocker, significantly reduced blood pressure in hypertensive patients while either maintaining or actually decreasing heart rate (HR). In this study, we exam- 1023)Key Words: azelnidipine, amlodipine, renal sympathetic nerve activity (RSNA), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
1
28
1
Order By: Relevance
“…In the present study, the azelnidipine-improved IS was associated with a significant reduction of SBP-LFamp. Although azelnidipine does not have an N-type calcium channel blocking action, it has a unique long-acting dihydropyridine-based calcium antagonistic action with sympathoinhibitory effects (29,30). Taken together, these results suggest that the sympathoinhibitory action is necessary for CCBs to exert a beneficial effect on IS.…”
Section: Sympathetic Activitymentioning
confidence: 91%
“…In the present study, the azelnidipine-improved IS was associated with a significant reduction of SBP-LFamp. Although azelnidipine does not have an N-type calcium channel blocking action, it has a unique long-acting dihydropyridine-based calcium antagonistic action with sympathoinhibitory effects (29,30). Taken together, these results suggest that the sympathoinhibitory action is necessary for CCBs to exert a beneficial effect on IS.…”
Section: Sympathetic Activitymentioning
confidence: 91%
“…Next, a catheter was inserted into the left external jugular vein for infusion of amlodipine (0.5 mg kg À1 , bolus injection; n¼5, Sigma-Aldrich Japan, Tokyo, Japan) or azelnidipine (0.1 mg kg À1 , bolus injection; n¼5, provided by Daiichi Sankyo, Tokyo, Japan). The dosage of amlodipine and azelnidipine was decided in reference to the procedure of Shokoji et al 15 A dorsal incision was then made under sterile conditions, and the left kidney was exteriorized. Glomerular microcirculation was recorded for 30 min after infusion by a charge-coupled device videomicroscope placed in direct contact with the exposed surface of the kidney, as described previously.…”
Section: Acute Administration Of Amlodipine and Azelnidipinementioning
confidence: 99%
“…It has been suggested that CCBs may activate the SNS and increase heart rates because of their potent hypotensive action (42,43). Unlike other dihydropyridine-type CCBs, AZ has a unique action of inhibiting SNS, and it indeed decreases, rather than increases, the heart rate after oral administration (6,44). Antihypertensive treatment with AZ attenuates reflex-induced sympathetic activation and enhances endothelial nitric oxide synthase expression levels in the brain as well as in the heart and aorta (45).…”
Section: Fig 2 the Correlation Between The % Change Of Blood Pressumentioning
confidence: 99%